1992
DOI: 10.1007/bf01249294
|View full text |Cite
|
Sign up to set email alerts
|

Relatedness and inbreeding in a French population of the unicolonial antIndomyrmex humilis (Mayr)

Abstract: SummaryWorker and queen samples of the Argentine ant Iridomyrmex humilis were analysed using allozyme electrophoresis. Two loci, peptidase and glucosephosphate isomerase, were found to be stainable and polymorphic. Both revealed an estimated relatedness in nestmate females that was close to zero, which is a consequence of the strong polygyny in this species. The inbreeding coefficient was found to be close to zero, which can be explained, in spite ofintra-nest mating taking place in L humilis, by the high mobi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
1

Year Published

1992
1992
2006
2006

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 17 publications
1
35
1
Order By: Relevance
“…Despite intranidal mating, the inbreeding coefficient and relatedness between sexuals are not significantly different from zero (Kaufmann et al 1992). Young queens shed their wings rapidly after mating and remain for a period in their natal nest, so that they are indistinguishable from old queens (Keller et al 1989).…”
Section: Linepithema Humilementioning
confidence: 99%
“…Despite intranidal mating, the inbreeding coefficient and relatedness between sexuals are not significantly different from zero (Kaufmann et al 1992). Young queens shed their wings rapidly after mating and remain for a period in their natal nest, so that they are indistinguishable from old queens (Keller et al 1989).…”
Section: Linepithema Humilementioning
confidence: 99%
“…Indeed, previous genetic studies on introduced L. humile populations failed to demonstrate a greater than zero relatedness among nestmate workers (Kaufmann et al 1992;Krieger and Keller 2000;Tsutsui and Case 2001;Ingram 2002a;Ingram and Gordon 2003) or gave equivocal results (Ingram 2002b).…”
mentioning
confidence: 99%
“…However, later studies showed polygyny as the principal social structure of many species (Pamilo & Rosengren, 1984;Kaufmann et al, 1992;Pamilo, 1993). In some species polygyny can be facultative (Seppä, 1992;Aron et al, 1999).…”
Section: Introductionmentioning
confidence: 99%